THE EFFECT OF USING WORDWALL APPLICATION IN IMPROVING STUDENT READING PROFICIENCY OF ELEVENTH GRADE STUDENTS AT SMA SWASTA KAMPUS NOMMENSEN PEMATANGSIANTAR - Yuly Winarti Gultom; Irene Adryani Nababan; Basar Lolo Siahaan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted based on the phenomenon that students’ reading proficiency, especially in understanding recount texts, was still relatively low. Many students experienced difficulties in comprehending vocabulary, identifying main ideas, and understanding the sequence of events. This problem was influenced by the use of teacher-centered methods and the lack of interactive learning media, which made students less engaged in the learning process. Therefore, this study aimed to determine whether the use of the Wordwall application had a significant effect on students’ reading proficiency. This research used a quantitative approach with a quasi-experimental design involving two groups: an experimental class and a control class. The population consisted of eleventh-grade students at SMA Swasta Kampus Nommensen Pematangsiantar, with a total sample of 52 students selected through purposive sampling. The instrument used was a reading test in the form of fill-in-the-blank questions administered through pre-test and post-test. The data were analyzed using mean, standard deviation, and t-test. The results showed that the mean score of the experimental class increased significantly from 38.07 in the pre-test to 86.73 in the post-test, while the control class only improved from 44.23 to 57.88. The t-test result (3.271) was higher than the t-table value (2.009), indicating that the alternative hypothesis was accepted. In conclusion, the Wordwall application is effective in improving students’ reading proficiency. It is recommended that teachers use Wordwall as an interactive learning medium, and future researchers are encouraged to apply it to other language skills.